Support of oral self-care, especially among patients with periodontitis - The role of dental hygienists and dental nurses - Järvinen, Mirkka (fi=Turun yliopisto|en=University of Turku|, 2020)
This study explores how to support the oral health and oral self-care of patients, especially patients with periodontitis. First, the current patient education practices of dental hygienists are described: their skills and knowledge related to patient education and the implementation of patient education in their work, with regard to both method and content (I). Then the acceptability of the oral health promotion program based on the transtheoretical model (TTM) is evaluated (II). Next, behavioral and educational interventions used to improve self-care in adult periodontitis patients are evaluated in comparison with conventional instruction (III). Last, the effectiveness of the motivational interview (MI) for the oral health and selfcare of patients with periodontitis in comparison with traditional education is determined (IV). In phase I, dental hygienists (n=222) answered the questionnaire. In phase II, the data were collected by dental hygienists and in-service trained dental nurses (n=28) involved in the health promotion program. In phase III, a systematic review was conducted, and in phase IV, the data were collected among adults with diagnosed periodontitis (n=28) randomly assigned to two groups (MI group and control group). The main findings are that dental hygienists regard patient education as important, and they seem to have the knowledge and skills for patient education in theory; however, some improvements should be made for patient education to become more effective, more patient-centered and more empowering (I). Dental professionals have a good attitude toward a novel patient education program based on the TTM. Training in new methods seems to increase their motivation to promote oral health, their evidence-based knowledge, and in some, their professional development (II). The behavioral interventions seem to be beneficial for patient adherence and may therefore improve initial periodontal treatment success (III). Patient education based on MI compared with professional-centered education seems to improve the oral health and self-care of patients with periodontitis (IV). As a conclusion: even brief training in the behavioral method for dental professionals can be sufficient. It can make patient education more empowering and, in that way, support the oral health and oral self-care of patients. Professionals’ own development in the use of the new method can happen step by step, adapting it naturally to their own practice.

Suun omahoidon tukeminen, erityisesti parodontiittipotilailla – suuhygienistien ja hammashoitajien rooli Tutkimuksessa tarkasteltiin miten potilaiden suun terveyttä ja omahoitoa voidaan tukea. Potilasohjauksen nykytilaa kuvattiin selvittämällä suuhygienistien näkemyksiä potilasohjaustiedoistaan ja taidoistaan. Toteutunutta potilasohjausta kuvattiin sisällöllisesti ja menetelmällisesti (I). Seuraavaksi arvioitiin transteoreettiseen muutosvaihemalliin pohjautuvan ohjausmenetelmän hyväksyttävyyttä suuhygienistien ja hammashoitajien keskuudessa (II) sekä potilasohjausinterventioita, joita on toteutettu parodontiittia sairastavien ohjauksessa (III). Lopuksi tutkittiin motivoivaan haastatteluun perustuvan ohjausmenetelmän vaikuttavuutta suun terveyteen ja omahoitoon parodontiittia sairastavilla, asiantuntijalähtöiseen ohjaukseen verrattuna (IV). Ensimmäinen aineisto kerättiin suuhygienisteiltä (n=222) puolistrukturoidulla kyselyllä. Toisessa vaiheessa aineisto kerättiin suuhygienisteiltä ja hammashoitajilta (n=28), jotka olivat osallistuneet uuden ohjausmenetelmän koulutukseen ja toteuttaneet sitä perheiden ohjauksessa. Kolmannessa vaiheessa toteutettiin systemoitu kirjallisuuskatsaus. Neljännessä vaiheessa tehtiin satunnaistettu kontrolloitu kliininen tutkimus, jossa parodontiittia sairastavat aikuiset (n=28) satunnaistettiin kahteen ryhmään (motivoiva haastattelu ja kontrolliryhmä). Suuhygienistit kokevat potilasohjauksen tärkeäksi sekä arvioivat taitonsa ja tietonsa hyviksi. Kehitettävää kuitenkin oli ohjauksen potilaslähtöisyydessä ja potilaan voimavaraistumisen tukemisessa (I). Suuhygienistit ja hammashoitajat suhtautuvat myönteisesti uuteen ohjausmenetelmään. He kokivat koulutuksen lisäävän heidän omaa motivaatiotaan, näyttöön perustuvaa tietoaan ja ammattitaitoaan (II). Motivoivaan haastatteluun perustuva potilasohjaus näyttää parantavan potilaiden suun terveyttä ja lisäävän omahoitoa, asiantuntijalähtöiseen ohjaukseen verrattuna (IV). Johtopäätöksenä todetaan, että lyhytkin suun terveydenhoidon ammattilaisille annettu käyttäytymistieteellisten menetelmien koulutus voi lisätä ohjauksen potilaslähtöisyyttä ja sitä kautta tukea potilaan motivaatiota ja omahoitoa. Ammattilaisen oma kehittyminen uuden menetelmän käytössä voi tapahtua vaiheittain, sitä omaan toimintaan luontevasti soveltaen.